Internal model control for industrial wireless plant using WirelessHART hardware-in-the-loop simulator - Tran, C.D. (ISA - Instrumentation, Systems, and Automation Society, 2018)
The emergence of wireless technologies such as WirelessHART and ISA100 Wireless for deployment at industrial process plants has urged the need for research and development in wireless control. This is in view of the fact that the recent application is mainly in monitoring domain due to lack of confidence in control aspect. WirelessHART has an edge over its counterpart as it is based on the successful Wired HART protocol with over 30 million devices as of 2009. Recent works on control have primarily focused on maintaining the traditional PID control structure which is proven not adequate for the wireless environment. In contrast, Internal Model Control (IMC), a promising technique for delay compensation, disturbance rejection and setpoint tracking has not been investigated in the context of WirelessHART. Therefore, this paper discusses the control design using IMC approach with a focus on wireless processes. The simulation and experimental results using real-time WirelessHART hardware-in-the-loop simulator (WH-HILS) indicate that the proposed approach is more robust to delay variation of the network than the PID. Â© 2017